2011
DOI: 10.1007/s12571-011-0152-1
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability in crisis: urban household food insecurity in Epworth, Harare, Zimbabwe

Abstract: Much of the contemporary literature on food security has focused on the rural sector. However, within the current context of high demographic growth, rapid urbanization and rising urban poverty which characterizes much of Sub-Saharan Africa, urban food insecurity cannot continue to be ignored. This study therefore examines the vulnerability of poor households to food insecurity in the challenging urban environment of Harare in Zimbabwe, an acute example of a city (and country) 'in crisis'. Findings from qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 19 publications
4
30
1
Order By: Relevance
“…Thus, a lower household income and increased family size tend to worsen household food insecurity. The findings from related studies done in Zimbabwe, Humbo and Sodo town agree with this finding [19,27,31,32]. The study also revealed as daily laborers were 16 times more likely to be food insecure compared to self-employed.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, a lower household income and increased family size tend to worsen household food insecurity. The findings from related studies done in Zimbabwe, Humbo and Sodo town agree with this finding [19,27,31,32]. The study also revealed as daily laborers were 16 times more likely to be food insecure compared to self-employed.…”
Section: Discussionsupporting
confidence: 84%
“…At the same time, there is also a possibility that the large family size may provide more working members, thereby decreasing the family's risk of being food‐insecure. Dependency ratio is, therefore, expected to be negatively associated with food security as it increases the number of people to be fed by a few working household members (Tawodzera, ).…”
Section: Concepts Of Women Empowermentmentioning
confidence: 99%
“…Dependency ratio is, therefore, expected to be negatively associated with food security as it Figure 1: Resource-agency-outcome empowerment framework Source: Adapted from Alsop and Heinson (2005) and Alsop et al (2006). increases the number of people to be fed by a few working household members (Tawodzera, 2011).…”
Section: Household-level Socioeconomic Determinants Of Food Securitymentioning
confidence: 99%
“…An estimated prevalence of 11.0% of the global population is undernourished and a higher 12.9% is observed in developing countries (FAO 2015). Food insecurity is not only limited to rural areas but is also observed in urban areas (Frimpong 2013;Tawodzera 2011). Rural to urban migration is usually associated with change consumption habits (Frimpong 2013;Puoane et al 2006).…”
Section: Introductionmentioning
confidence: 99%